1998
DOI: 10.1123/jsep.20.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Sport-Confidence: Conceptualization and Instrument Development

Abstract: The purposes of this study were to identify sources of self-confidence in athletes within the sport-confidence framework of Vealey (1986, 1988), develop a reliable and valid measure of sources of sport-confidence, and extend the conceptual framework of sport-confidence to include sources and test predictions within the expanded model. In Phases 1, 2, and 3 of the study, the preliminary conceptual basis for sources of sport-confidence was developed and initial psychometric evidence supported the factor structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
191
4
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(227 citation statements)
references
References 0 publications
11
191
4
4
Order By: Relevance
“…The findings of the present study emphasize the importance of the sources of sport confidence identified by Hays et al (2007) and Vealey et al (1998), as these would seem imperative to the confidence of athletes. The sources from which athletes derive their confidence are not only sport specific, but also influenced by demographic and organizational factors.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The findings of the present study emphasize the importance of the sources of sport confidence identified by Hays et al (2007) and Vealey et al (1998), as these would seem imperative to the confidence of athletes. The sources from which athletes derive their confidence are not only sport specific, but also influenced by demographic and organizational factors.…”
Section: Discussionmentioning
confidence: 82%
“…Thus, it is perhaps not surprising that the study of self-confidence has featured prominently in sport psychology literature, with social cognitive theories such as Bandura's (1977) self-efficacy theory and Vealey's (1986Vealey's ( , 1998Vealey's ( , 2001) models of sport confidence providing the basis for most of this work. Vealey provided the first model of sport confidence in 1986 in an attempt to develop a sport-specific framework and inventories to operationalize confidence in competitive sport.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, environmental comfort and 21 situational favourableness are reported to be sources of sport confidence (Vealey et al, 1998), 22 which in turn provides a foundation for flow occurrence. Positive feedback increased confidence for these players, and in particular, intrinsic 6 feedback was reported to be relevant for flow occurrence: Not so much hitting a good shot but getting a feeling: "oooh that felt easy to do...that which is the hard bit and that...only comes through hard work and dedication.…”
mentioning
confidence: 99%